The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 20th International Conference on Intelligent User Interfaces 2015
DOI: 10.1145/2678025.2701382
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Detection of Divided Attention in Reading Applications Using EEG and Eye Tracking

Abstract: Reading is central to learning and communicating, however, divided attention in the form of distraction may be present in learning environments, resulting in a limited understanding of the reading material. This paper presents a novel system that can spatio-temporally detect divided attention in users during two different reading applications: typical document reading and speed reading. Eye tracking and electroencephalography (EEG) monitor the user during reading and provide a classifier with data to decide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…For instance, the stable “in the zone” state in gradCPT was shown to be related to moderate DMN activity. On the other hand, CS researchers usually focused on different aspects of attention stimuli and defined attention within a specific context [ 11 , 89 , 90 ], e.g., the divided attention research in video learning [ 11 ] focused on only two stimuli of distraction—multitasking and environmental noise—and this potentially limits its generalization to other contexts. In our work, we distinguish attention states based on a RTV analysis in gradCPT, depending less on distractions or other environmental factors.…”
Section: Overall Discussionmentioning
confidence: 99%
“…For instance, the stable “in the zone” state in gradCPT was shown to be related to moderate DMN activity. On the other hand, CS researchers usually focused on different aspects of attention stimuli and defined attention within a specific context [ 11 , 89 , 90 ], e.g., the divided attention research in video learning [ 11 ] focused on only two stimuli of distraction—multitasking and environmental noise—and this potentially limits its generalization to other contexts. In our work, we distinguish attention states based on a RTV analysis in gradCPT, depending less on distractions or other environmental factors.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Similarly, research concerning the association between divided attention and physiological parameters is rare. The only research work on investigating divided attention in correlation with EEG power bands was conducted by Rodrigue et al (2015). The study was aimed to determine the level of divided attention of users using the Emotiv EPOC device and concluded that the (black-box) algorithm implemented in this device was considered and deemed reliable.…”
Section: State Of the Art Of Physiological Approaches To Measuring Attentionmentioning
confidence: 99%
“…Such a system could be used to manage educational content based on the level of attention the child keeps with the instructional material. A more robust technology-based approach is proposed by [15] to detect divided attention in reading activities. While children were reading the environment was fueled with distractors in the format of multitasking instructions or environmental noise.…”
Section: Related Workmentioning
confidence: 99%